ANALISIS KEMISKINAN BERDASARKAN FAKTOR TINGKAT PENDIDIKAN DAN INDEKS PEMBANGUNAN MANUSIA (IPM) PROVINSI ACEH - Fitri Yanti (LPPM IAI Almuslim Aceh, 2023)
Poverty can be seen from the standard of decent living, meaning that we see whether a person or family is able to meet their basic needs. It is further interpreted that poverty is a condition where basic needs or basic needs are not met so that a decent standard of living is not achieved. The basic needs referred to are food, clothing, housing or shelter, education and health. This research aims to analyze poverty based on the level of education factors and the Human Development Index (PMI) which influence poverty in the province of Aceh. The research method used in this research is descriptive quantitative using secondary data obtained from the Central Statistics Agency (BPS). The results of this research show that the level of education and the Human Development Index influence poverty in Aceh Province. The higher the level of education and the Human Development Index, the lower the poverty rate.